Prognostic markers in core‐binding factor AML and improved survival with multiple consolidation cycles of intermediate‐/high‐dose cytarabine. (6th June 2018) - Prabahran, Ashvind; Tacey, Mark; Fleming, Shaun; Wei, Andrew; Tate, Courtney; Marlton, Paula; Wight, Joel; Grigg, Andrew; Tuckfield, Annabel; Szer, Jeff; Ritchie, David; Chee, Lynette
Abstract: Objectives: Core‐binding factor acute myeloid leukaemia (CBF AML) defined by t (8;21)(q22;q22) or inv(16)(p13q22)/ t (16;16)(p13;q22) has a favourable prognosis; however, 30%‐40% of patients still relapse after chemotherapy. We sought to evaluate the risk factors for relapse in a de novo CBF AML cohort. Patients/Materials/Methods: A retrospective review of patients from four Australian tertiary centres from 2001 to 2012, comprising 40 t (8;21) and 30 inv(16) AMLs. Results: Multivariate analysis identified age ( P = .032) and white cell count (WCC)>40 ( P = .025) as significant predictors for inferior OS and relapse, respectively. Relapse risk was higher in the inv(16) group vs the t (8;21) group (57% vs 18%, HR 4.31, 95% CI: 1.78‐10.42, P = .001). Induction therapy had no bearing on OS or relapse‐free survival (RFS); however, consolidation treatment with >3 cycles of intermediate‐/high‐dose cytarabine improved OS ( P = .035) and RFS ( P = .063). Five patients demonstrated post‐treatment stable q PCR positivity without relapse. Conclusions: >3 consolidation cycles of intermediate‐/high‐dose cytarabine improves patient outcomes Age and inv(16) CBF AML subtype are predictors of inferior OS and RFS, respectively. Stable low‐level MRD by qPCR does not predict relapse Similar OS in the inv(16) cohort compared to the t (8;21) cohort, despite a higher relapse rate, confirms salvageability of relapsed disease.